2020
DOI: 10.1111/jce.14791
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the prevalence of intracardiac thrombus on the first presentation of atrial fibrillation versus flutter in the pediatric and congenital heart disease population

Abstract: Introduction: Guidelines recommend trans-esophageal echocardiography (TEE) for patients with atrial fibrillation (AF) or atrial flutter (AFL) for >48 h, due to risk of intracardiac thrombus formation. With growing evidence that AFL in adults with structurally normal hearts has less thrombogenic potential compared to AF, and the need for TEE questioned, we compared prevalence of intracardiac thrombus detected by TEE in pediatric and congenital heart disease (CHD) patients presenting in AF and AFL. Methods/Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Atrial tachycardia is electromechanically different from AF, and differences in atrial contraction likely carry significantly different thromboembolic risks. 22 In a study investigating LAA thrombus, SEC was detected in low-risk patients with younger age and low CHA 2 DS 2 -VASc scores and LAVI values who did not take anticoagulants and had AFL, while no thrombus was detected in any of them. 23 In contrast, in our study, when examining patients with thrombus, it was observed that the AT type was predominantly sustained, more common in females, mostly occurring in individuals aged 65 and above, with high CHA 2 DS 2 -VASc scores and elevated LAVIs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Atrial tachycardia is electromechanically different from AF, and differences in atrial contraction likely carry significantly different thromboembolic risks. 22 In a study investigating LAA thrombus, SEC was detected in low-risk patients with younger age and low CHA 2 DS 2 -VASc scores and LAVI values who did not take anticoagulants and had AFL, while no thrombus was detected in any of them. 23 In contrast, in our study, when examining patients with thrombus, it was observed that the AT type was predominantly sustained, more common in females, mostly occurring in individuals aged 65 and above, with high CHA 2 DS 2 -VASc scores and elevated LAVIs.…”
Section: Discussionmentioning
confidence: 97%
“…Clinicians are more concerned with the risk of thrombus presence in the LA/LAA before radiofrequency ablation to determine the need for preprocedural anticoagulation and TEE in patients with AT, rather than whether these patients need anticoagulant therapy. Atrial tachycardia is electromechanically different from AF, and differences in atrial contraction likely carry significantly different thromboembolic risks 22 . In a study investigating LAA thrombus, SEC was detected in low‐risk patients with younger age and low CHA 2 DS 2 ‐VASc scores and LAVI values who did not take anticoagulants and had AFL, while no thrombus was detected in any of them 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, treatment may involve medications, cardiac pacing, cardioversion, radio-frequency catheter ablation, or surgical procedures. The guidelines recommend trans-esophageal echocardiography (TEE) for patients with atrial fibrillation (AF) or atrial flutter (AFL) for >48 h, due to the risk of intracardiac thrombus formation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%